Respuesta :

remember you can do anything to an equaiton as long as you do it to both sides
2x(3x-1)=7
first, distribute, (a(b-c)=ab-ac)
6x^2-2x=7
minus 7 from both sides
6x^2-2x-7=0
use quadratic equation
for
ax^2+bx+c=0
x=[tex] \frac{-b+/- \sqrt{b^2-4ac} }{2a} [/tex]

6x^2-2x-7
a=6
b=-2
c=-7

x=[tex] \frac{-(-2)+/- \sqrt{(-2)^2-4(6)(-7)} }{2(6)} [/tex]
x=[tex] \frac{2+/- \sqrt{4+168} }{12} [/tex]
x=[tex] \frac{2+/- \sqrt{172} }{12} [/tex]
x=[tex] \frac{2+/- 2\sqrt{43} }{12} [/tex]
x=[tex] \frac{1+/- \sqrt{43} }{6} [/tex]


x=[tex] \frac{1+ \sqrt{43} }{6} [/tex] and [tex] \frac{1- \sqrt{43} }{6} [/tex]